Implementasi Digital Marketing Terhadap Perkembangan UMKM Di Huntap Pombewe Kabupaten Sigi - Barkat Ansari; Syamsul Bachri; Ira Nuriya Santi; Farid Farid (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy by significantly contributing to Gross Domestic Product (GDP) and employment. This study aims to explore the impact of using digital marketing on sales, marketing strategies, and obstacles faced by MSME players in Pombewe Huntap. The triangulation method is used to ensure data validity by collecting information from various sources, methods, and theories. The research population involves MSME players in Pombewe Huntap who have implemented digital marketing in selling their products. The difference in income after using digital marketing can be seen from the increase in product sales, because it reaches a wider market, including the Sigi Regency and Palu City areas. The obstacles faced involve network constraints, which affect the display of images and the attractiveness of live streaming sales. The results show that digital marketing has a positive effect on the sales and marketing strategies of MSMEs in Pombewe Huntap. Although there are several obstacles such as unstable internet connections, delivery delays, transaction fraud, and manipulation of admin numbers, the application of digital marketing provides tangible benefits in increasing marketing and sales of MSME products.